Assessment of trimethoprim-sulfamethoxazole susceptibility testing methods for fastidious Haemophilus spp. - Sierra, Y. (2020)
Background: Several discrepancies were found in clinical routine regarding trimethoprim-sulfamethoxazole (SXT) susceptibility determination depending on antimicrobial susceptibility (AST) method used and growth media. We aimed to compare the determinants of SXT resistance with established susceptibility values for fastidious Haemophilus spp., in order to provide recommendations for optimal SXT measurement. Materials/methods: We collected 50 strains each of Haemophilus influenzae and Haemophilus parainfluenzae at Bellvitge University Hospital. SXT susceptibility was tested by microdilution, E-test, and disc diffusion using both Mueller-Hinton Fastidious (MH-F) and Haemophilus Test Medium (HTM) following EUCAST and CLSI criteria respectively. Mutations in folA, folP and additional determinants of resistance were identified in whole-genome sequenced isolates. Results: Strains presented generally higher rates of SXT resistance when grown on HTM than on MH-F, independent of the methodology used (average MIC 2.6-fold higher in H. influenzae and 1.2-fold higher in H. parainfluenzae). The main resistance-related mechanisms were as follows: I95L and F154S/V in FolA; 3 and 15 base pair insertions and substitutions in folP; acquisition of sul genes; and FolA overproduction potentially linked to mutations in -35 and -10 promoter motifs. Of note, 2 of 19 H. influenzae strains (10.5%) and 9 of 33 H. parainfluenzae strains (27.3%) with mutations and assigned as resistant by microdilution were inaccurately considered susceptible by disc diffusion. This misinterpretation was resolved by raising the clinical resistance breakpoint of the EUCAST guidelines to ≤30 mm. Conclusions: Given the routine use of disc diffusion, a significant number of strains could potentially be miscategorised as susceptible to SXT despite having resistance-related mechanisms. A simple modification to the current clinical resistance breakpoint given by the EUCAST guideline for MH-F ensures correct interpretation and correlation with the gold-standard method of microdilution.